The Study of Mouth Washing Duration with Boiled Uncaria gambir on the Dental Plague Formation - Susilowati, Aning; Sumarawati, Titiek (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Dental plague has been known to be the major agent causing dental carries and periodontal disease which are the most common dental and soft tissue diseases with the prevalence of 70-80%. The preventive measure including the use of chemical substance of catechin having anti-plague activity in the form of mouth wash has been shown to have effects on the dental plague formation. The objective of this study was to find out the duration of mouth washing with boiled gambir (Uncaria ambir) on the plague formation in Pondok Pesantren Al-Badriyah Mranggen, Demak.Design and Method: In this study using Pretest-Posttest Control Group Design, 44 samples of subjects was divided into 4 groups of 11 each. Group I, II, II were treated with the mouth wash of Uncaria gambir boiled 2, 3, 4 minutes respectively. Group IV serving as control was treated with mouth wash of water for 3 minutes. The data was analyzed with non parametric test using Kruskal-Wallis followed by Mann-Whitney test with p < 0.05.Result: Kruskal Wallis analysis showed a significant difference in mean of plague before and after the treatment among the four groups (p < 0.05). Mann-Whitney test showed no significant difference between group I and III ( p> 0.05) and significant difference for the rest of the groups (p < 0.05). Conclusion: The mouth rinse duration using boiled Gambir has been shown to have an effect on the dental plague formation. 3 minute mouth washing shows the optimum effect (Sains Medika, 4(1):57-62).